Hubungan antara Zea mays L., Ostrinia furnacalis (Lep.:Pyralidae) dan Beauveria bassiana Vuill. - Itji Diana Daud (Jurnal Entomologi Indonesia, 2005)
Connection between Zea mays L., Ostrinia furnacalis (Lep.:Pyralidae) and  Beauveria bassiana Vuill. The entomopatogen fungus, Beauveria bassiana (Balsamo), is obtained in the tissue of corn plant through submersion of seed in cinidia 1010/ml. Tissue observation showed that hifa B. bassiana appears when the plant attain the age of three weeks and when it reaches six weeks B bassiana appears in all sample plants. Hifa obtained in parenchyma tissue passively without causing illness the mother plant. The appearance of B. bassiana is remained until the 12th weeks of plant. Bio test of plan which contain the endofit of B. bassiana showed the percentage of tested insect mortality is 64%. The observation showed that the corn plant can still produce the toxin of beauverisin.